The Implementation of Learning Media: Quizizz Application in EFL Remote Learning - Indrayana, Ida Bagus Ade (Universitas Pendidikan Ganesha, 2022)
During Pandemic of Covid-19, the teachers require to improve their skill in using the technology to conduct the remote teaching-learning process more conducive. Therefore, the teachers need to master using the technology besides their material. Quizizz is one kind of application that can support the teaching-learning process because it has many interesting features in it. The aims of this research are to analyse the effectiveness of Quizizz to implement during the remote teaching-learning process. The instrument use a questionnaire which was responded to by 88 students and conducting an interview with one English teacher. The method in this research is using descriptive qualitative research. The results show that Quizizz is effective and appropriate to be implemented during the remote teaching-learning process. The use of Quizizz as the learning media was running well without any problems where the teacher provided the materials, exercises, and the result of the exercises as well with the instruction to make the students know what they should do. Moreover, the remote teaching implementation by using Quizizz as the learning media is recommended because it is really fun, easy to use, and makes the remote class more active.